PENGARUH PUPUK ORGANIK BIO-SLURRY DAN MULSA SERBUK GERGAJI TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI MAIN NURSERY - Yepta Maruntung Aritonang; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The aim of this research is to know the interaction of bio-slurry organic fertilizer and mulch saws and the best dosage to the growth of oil palm seedlings in Main Nursery. The research was conducted in experimental station and the soil laboratory, Faculty of Agriculture, Riau University, Pekanbaru. The research was conducted in September – December 2016. The research was factorial experiment that arrangge by Randomized Complete Design (RAL) with treatment of 2 factors with 3 replications. The first treatment factor was the dosage of bio-slurry organic fertilizer,  0 g.plant solid bio-slurry (B0), 25 g.plant solid bio-slurry (B1) and 50 g.plant bio-slurry (B2). The second treatment factor was mulch sawdust, sawdust dose 0 g.plant (M0), sawdust dose 100 g.plant (M1) and sawdust 200 g.plant dose (M2). The results showed that the interaction of dense bio-slurry and mulch sawdust effect on nitrogen content in the leaves remained not to other parameters. Giving solid bio-slurry dose 50 g.plant and mulch sawdust 200 g.plant dose is the best treatment that can increase the growth of oil palm seedlings. Keywords: Palm oil, Main Nursery, solid bio-slurry, sawdust